Part 1: Optimization and evaluation of dynamic trajectory radiotherapy. Issue 9 (27th July 2018) - Fix, Michael K.; Frei, Daniel; Volken, Werner; Terribilini, Dario; Mueller, Silvan; Elicin, Olgun; Hemmatazad, Hossein; Aebersold, Daniel M.; Manser, Peter
Abstract : Purpose: Although volumetric modulated arc therapy (VMAT) is a well‐accepted treatment technique in radiotherapy using a coplanar delivery approach, VMAT might be further improved by including dynamic table and collimator rotations leading to dynamic trajectory radiotherapy (DTRT). In this work, an optimization procedure for DTRT was developed and the potential benefit of DTRT was investigated for different treatment sites. Methods: For this purpose, a dedicated optimization framework for DTRT was developed using the Eclipse Scripting Research Application Programming Interface (ESRAPI). The contours of the target and organs at risk (OARs) structures were exported by applying the ESRAPI and were used to determine the fractional volume‐overlap of the OARs with the target from several potential beam directions. Thereby, an additional weighting was applied taking into account the relative position of the OAR with respect to the target and radiation beam, that is, penalizing directions where the OAR is proximal to the target. The resulting two‐dimensional gantry‐table map was used as input for an A* path finding algorithm returning an optimized gantry‐table path. Thereby, the process is also taking into account CT scan length and collision restrictions. The A* algorithm was used again to determine the dynamic collimator angle path by optimizing the area between the MLC leaves and the target contour for each gantry‐table path leading to gantry‐collimator paths. The resulting gantry‐table and gantry‐collimator paths are combined and serve as input for the intensity modulation optimization using a research VMAT optimizer and the ESRAPI resulting in dynamic trajectories. This procedure was evaluated for five clinically motivated cases: two head and neck, one lung, one esophagus, and one prostate. Final dose calculations were performed using the Swiss Monte Carlo Plan (SMCP). Resulting dose distributions for the DTRT treatment plans and for the standard VMAT plans were compared based on dose distributions and dose volume histogram (DVH) parameters. For this comparison, the dose distribution for the VMAT plans were recalculated using the SMCP. In addition, the suitability of the delivery of a DTRT treatment plan was demonstrated by means of gafchromic film measurements on a TrueBeam linear accelerator. Results: DVHs for the target volumes showed similar or improved coverage and dose homogeneity for DTRT compared with VMAT using equal or less number of dynamic trajectories for DTRT than arcs for VMAT for all cases studied. Depending on the case, improvements in mean and maximum dose for the DTRT plans were achieved for almost all OARs compared with the VMAT plans. Improvements in DTRT treatment plans for mean and maximum dose compared to VMAT plans were up to 16% and 38% relative to the prescribed dose, respectively. The measured and calculated dose values resulted in a passing rate of more than 99.5% for the two‐dimensional gamma analysis using 2% and 2 mm criteria and a threshold of 10%. Conclusions: DTRT plans for different treatment sites were generated and compared with VMAT plans. The delivery is suitable and dose comparisons demonstrate a high potential of DTRT to reduce dose to OARs using less dynamic trajectories than arcs, while target coverage is preserved.